Study on applicability of Death Attitude Profile-Revised in medical students (死亡态度描绘量表在医学生中的适用性研究) - CHEN Qiannan (陈倩楠); ZHANG Jing (张静); QIAN Zhigang (钱志刚) (Association of Integrative Nursing, 2021)
Objective To explore the applicability of Death Attitude Profile-Revised (DAP-R) in medical students. Methods Totally 850 medical students were selected by convenience sampling method, and investigated by general situation questionnaire and DAP-R. The response distribution, extreme value and correlation between each item score and total score were analyzed in project analysis. The reliability of the scale was evaluated by internal consistency using Cronbach's α and split-half reliability coefficient using Spearman-Brown coefficient. The validity of the scale was evaluated by content and structural validity. Results The response distribution of each item was not skewed. Except for items related to natural acceptance dimensions, CR values of other items were all greater than 3 and P was less than 0. 05, and correlation coefficient (r value) between items and total scale was greater than 0. 3. The Cronbach's α of the total scale was 0. 911, and the Cronbach's coefficient of the dimension ranged from 0. 794 to 0. 897. The split-half reliability coefficient of the total scale was 0. 89, and the split-half reliability coefficient of the dimension ranged between 0. 773 and 0. 860. The r value between dimension and corresponding items represented the validity of the scale contents (0. 531~0. 880). Exploratory factor analysis and internal correlation were used to evaluate the structural validity of the scale. The KMO value was 0. 930>0. 6, and the approximate chi-square value of Bartlett ball test was 15023. 416, P < 0. 05. Exploratory factor analysis showed that the factors extracted from the five characteristic roots >1, and the cumulative variance contribution rate was 61. 436%. Except for item 1, the load of other items on the corresponding factor was greater than 0. 4. In addition to the naturally accepted dimension, the r value of other dimensions ranged from 0. 208 to 0. 709, and the r value between dimension and total scale ranged from 0. 663 to 0. 834. Conclusion The DAP-R has good reliability among medical students, but its validity is moderate. Further researchers are required to verify the applicability of DAP-R scale in medical students. (目的 探讨死亡态度描绘量表在医学生中的适用性。方法 采用便利抽样法抽取850名医学生, 使用一般情况调查表、死亡态度描绘量表(DAP-R)进行调查。采用答案分布法、极端值法、条目总分相关法进行项目分析, 通过内部一致性Cronbach's α系数、折半信度Spearman-Brown系数评价量表信度, 通过内容效度及结构效度评价量表效度。结果 各条目答案分布没有呈偏态分布; 除自然接受维度相关条目外, CR值均＞3且P＜0. 05, 条目与总量表r值＞0. 3。总量表Cronbach's α系数为0. 911, 维度Cronbach'sα系数为0. 794~0. 897; 总量表折半信度系数为0. 89, 维度折半信度系数为0. 773～0. 860。维度与相应条目r值为0. 531~0. 880。采用探索性因子分析和量表内部相关性评价量表的结构效度, KMO值为0. 930＞0. 6, Bartlett球型检验近似卡方值为15023. 416, P＜0. 05; 探索性因子分析显示提取5个特征根>1的因子, 累积方差贡献率为61. 436%; 除条目1外, 其余条目在相应因子上载荷均大＞0. 4; 除自然接受维度, 其余维度r为0. 208~0. 709, 维度与总量表的r为0. 663~0. 834。结论 DAP-R在医学生中具有较好的信度, 然而效度一般, 有待于进一步验证DAP-R量表在医学生中的适用性。)